A numerical comparative study of the effect of working fluids and wick properties on the performance of capillary pumped loop with a flat evaporator. (5th May 2016) - Boubaker, Riadh; Platel, Vincent; Harmand, Souad
Highlights: A complete dynamic model of a capillary pumped loop is presented. The heat and mass transfer inside the porous wick is described by a 2D mathematical model. Effects of the thermophysical properties of working fluids are extensively analyzed. Effects of the porous wick properties on the CPL performance are investigated. Abstract: This study presents a numerical analysis of a capillary pumped loop (CPL) performance using different working fluids and porous wick properties. A complete CPL model is used, which describes the growth of the vapor pocket inside the porous wick. The CPL behavior is studied for different working liquids, such as methanol, acetone and ethanol. Results show that methanol is the most efficient fluid in terms of thermal conductance and heat transport capacity. The present work allows also to evaluate the importance of the wick properties in the improvement of the thermal characteristics for capillary pumped loop.